Hybrid Molecules as Potential Drugs for the Treatment of HIV: Design and Applications - Wissal Liman; Nouhaila Ait Lahcen; Mehdi Oubahmane; Ismail Hdoufane; Driss Cherqaoui; Rachid Daoud; Achraf El Allali (MDPI AG, 2022)
Human immunodeficiency virus (HIV) infection is a major problem for humanity because HIV is constantly changing and developing resistance to current drugs. This necessitates the development of new anti-HIV drugs that take new approaches to combat an ever-evolving virus. One of the promising alternatives to combination antiretroviral therapy (cART) is the molecular hybrid strategy, in which two or more pharmacophore units of bioactive scaffolds are combined into a single molecular structure. These hybrid structures have the potential to have higher efficacy and lower toxicity than their parent molecules. Given the potential advantages of the hybrid molecular approach, the development and synthesis of these compounds are of great importance in anti-HIV drug discovery. This review focuses on the recent development of hybrid compounds targeting integrase (IN), reverse transcriptase (RT), and protease (PR) proteins and provides a brief description of their chemical structures, structure-activity relationship, and binding mode.